Effectiveness of tocilizumab in the treatment of hospitalized adults COVID-19: A systematic review and meta-analysis. Issue 9 (4th March 2022) - Zhang, Jing; Chen, Chun; Yang, Yi; Yang, Jin
Abstract: Background: Since December 2019, the coronavirus disease (COVID-19) has spread worldwide, leading to a global health threat. This study aimed to investigate the effectiveness of tocilizumab in COVID-19 patients. Methods: We systematically searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, and World Health Organization International Clinical Trials Registry Platform to March 10, 2021 for randomized controlled trials in which patients were randomly assigned to receive tocilizumab plus usual care or usual care alone in hospitalized adults with COVID-19. A random-effects meta-analysis model was used to pool studies. All data analyses were performed using Review Manager version 5.4. Results: Eleven studies with 6579 patients were included in our meta-analysis, of which 3406 and 3173 were assigned to tocilizumab and control groups, respectively. Tocilizumab significantly reduced the 28 to 30-day mortality (relative risk [RR] = 0.89, 95% confidence interval [CI] 0.80-0.99, P = .04), incidence of mechanical ventilation (MV) (RR = 0.79, 95% CI 0.71-0.89, P < .001), composite outcome of MV or death (RR = 0.81, 95% CI 0.72-0.90, P < .001), time-to-hospital discharge (hazard ratio = 1.30, 95% CI 1.16-1.45, P < .001), intensive care unit admission (RR = 0.64, 95% CI 0.47-0.88, P = .006), serious infection (RR = 0.61, 95% CI 0.40-0.94, P = .02), and number of serious adverse events (RR = 0.64, 95% CI 0.47-0.86, P = .004). Conclusion: Tocilizumab reduced short-term mortality, incidence of MV, composite outcome of death or MV, intensive care unit admission, serious infection, serious adverse events, and time-to-hospital discharge in hospitalized COVID-19 patients. Further studies are required to determine the optimal dose.